Bulk geochemistry of composite sediment core ROD11 from the crater basin of Rodderberg, Germany - Bernd Zolitschka; Manfred Frechen (PANGAEA, 2025)
Bulk geochemistry characterizes sediment composition and supports palaeoclimatic reconstruction of glacial/interglacial cycles for the Middle Pleistocene sediment record from the crater basin of Rodderberg, Germany. A sediment record measuring 72.8 m in length was retrieved by employing wire-line drilling techniques, utilising 3 m-long liners, from the silted-up crater basin of Rodderberg (East Eifel Volcanic Field) in the vicinity of the city of Bonn, Germany. The composite record ROD11 was subjected to continuous analysis for bulk geochemistry (total carbon, total nitrogen, total sulphur) with 10 cm spatial resolution employing a CNS analyser (EuroEA, Eurovector). Additionally, the analysis of total organic carbon was carried out with the same setup but after the destruction of carbonates with 3% and 20% sulphuric acid. The difference between total carbon and total organic carbon yields total inorganic carbon, a proxy parameter for carbonates. The calculation of organic matter was performed by multiplication of total organic carbon with a value of 2.13, in accordance with the methodology proposed by Dean (1974). The calculation of carbonaceous matter was accomplished by multiplying total inorganic carbon values with 8.33, in order to account for the stoichiometric mass change from C to CaCO3. Minerogenic matter was determined as the difference between 100 and the sum of organic matter and carbonaceous matter. These parameters enhance the palaeoclimatic interpretation for the past 430 ka. Valued by multiple dating techniques, this terrestrial record provides an environmental reconstruction since the Middle Pleistocene.